Die Neuerwerbungen äthiopischer Handschriften der Völkerkundlichen Sammlungen der Stadt Mannheim im Reiss-Museum - Six, Veronika (Aethiopica, 2000)
Description of five Ethiopic manuscripts which were given to the Reiss-Museum in Mannheim, Germany, after the publication of vol. XX 6 in the year 1994 and vol. XX 3 in 1999 of the Ethiopian series of VOHD (= Verzeichnis der orientalischen Handschriften in Deutschland) compiled by the same authoress.